DOES SIZE MATTER?: Technical Efficiency and Industry Size in Indonesia - Richard V. Llewelyn, Richard V.; Sutrisno, Wang (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2002)
The debate over which size industry is best suited for Indonesiacontinues with proponents of both large and small sizes pointing out the benefits of each. However, little empirical analysis has been done regarding economic matters such as technical efficiency. Nonparametric analysis of technical efficiency for three sizes of firms in seven manufacturing sectors is estimated using linear programming techniques. Aggregated input and output data from BPS from 1991 to 1997 are used.Household size firms are found to be most efficient relative to the other sizes for five of the seven sectors analyzed. Large firms are relatively more efficient in âFood, Beverage, and Tobaccoâ sector. Small companies are relatively less efficient than household firms in all but one case, but relatively more efficient than large firms in five of seven sectors. The results validate and perhaps explain the duel economy in Indonesia with both large and small firms existing in the same industry.When each sector is analyzed for each firm size, the âNon-MetallicMineral Products Other Than Petroleum and Coalâ sector is most efficient for all sizes of firms. The least efficient sector is the âChemical and Plasticsâ industry.The results suggest that government policy should be focused oncreating a stable environment for business, which promotes growth of efficient businesses, either large or small. Specific policies and intervention for small business development are not necessary, given the relative efficiency of small firms in Indonesia.